(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the diverse of translation practices, examining various types of translations across different linguistic contexts especially used by Uzbek translators. It investigates the nuances and challenges inherent in translation processes, ranging from word-for-word translations to adaptations tailored to specific cultural and linguistic norms. By exploring examples and scholarly perspectives, the article sheds light on the complexities involved in conveying meaning accurately across languages. It underscores the importance of understanding the distinct characteristics of each translation type and the significance of employing appropriate strategies to ensure fidelity to the original text. Overall, the article can serve as a comprehensive exploration of the multifaceted nature of translation endeavors.